ONLINE LEARING DURING COVID-19 PANDEMIC: SURVEY AMONG UNIVERSITY STUDENTS TOWARDS USAGE OF VIDEO-BASED LEARNING - Jelani, Ahmad Bakhtiar; Said, Che Soh; Mohamad, A Nasorudin; Mohd Nor, Ahmad Firdaus; Mohd Nor, Saidi Adnan (Jurnal 'Ulwan, 2023)
The purpose of this study was to explore the use of video-based learning in online learning environments during the COVID-19 pandemic. This study uses a quantitative research method with a cross-sectional survey design. The study sample consisted of 306 students from four universities in Peninsular Malaysia. Data collection was done online using instruments based on the technology acceptance model. Descriptive analysis reporting the mean and frequency showed that respondents had a positive attitude towards the use of video in online learning. Based on the results of this study, it is suggested that the use of video in online learning be enriched and lengthened to support the aims of the curriculum. In conclusion, video-based learning is an effective educational tool for improving students' performance during COVID-19.